2022
DOI: 10.1037/edu0000522
|View full text |Cite
|
Sign up to set email alerts
|

Do peers matter? Peer effects on young children’s vocabulary gains in German classrooms.

Abstract: Children in early childhood education and care (ECEC) spend a considerable amount of time interacting with their peers. However, open questions remain on whether and how children influence their peers' language development. The present study examined effects of peers' German receptive vocabulary (n = 1,871) on individual children's (n = 431) receptive vocabulary gains. Target children were between 30 and 48 months old at the beginning of the study. Findings revealed no links between peers' vocabulary skills an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 57 publications
1
8
1
Order By: Relevance
“…Similarly, peer language skills in the fall had the greatest influence on those preschoolers whose initial language skill was one standard deviation lower than the class mean (Justice et al, 2011). The null effect of the interaction between peer language skills and DLL status on the growth of English expressive vocabulary is consistent with other studies (e.g., Kohl et al, 2022), suggesting that emergent and FBs’ English language growth is influenced by classroom language contexts the same way as EMs. One possible explanation is that DLLs are more heterogeneous in their linguistic, cultural, and socioeconomic backgrounds than they are in their English expressive vocabulary.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similarly, peer language skills in the fall had the greatest influence on those preschoolers whose initial language skill was one standard deviation lower than the class mean (Justice et al, 2011). The null effect of the interaction between peer language skills and DLL status on the growth of English expressive vocabulary is consistent with other studies (e.g., Kohl et al, 2022), suggesting that emergent and FBs’ English language growth is influenced by classroom language contexts the same way as EMs. One possible explanation is that DLLs are more heterogeneous in their linguistic, cultural, and socioeconomic backgrounds than they are in their English expressive vocabulary.…”
Section: Discussionsupporting
confidence: 89%
“…Contrary to the abovementioned studies, other studies such as Weiland and Yoshikawa’s (2014), Choi, Castle, et al (2018), and Kohl et al (2022) did not show a significant association between peer language skills and DLLs’ language development. These studies reported a null effect of peer language skills on the growth of receptive vocabulary in young toddlers and preschool children, after controlling for child-level (e.g., baseline language skills, self-regulation), peer-level (e.g., proportion of DLLs, proportion of low-income children, mean maternal education) and classroom level (e.g., classroom quality) factors.…”
Section: Research Backgroundcontrasting
confidence: 81%
See 2 more Smart Citations
“…Our results are consistent with the existing literature, given that fried chicken, burgers and other fast food are typically meat-based. Secondly, although it has been found in the literature that younger students are more susceptible to peer effects [ 66 ], this difference is more present in peer effects on cognitive abilities such as academic performance [ 79 ]. In terms of food consumption, older students are more likely to be influenced by peer effects because they may have more money available to them.…”
Section: Discussionmentioning
confidence: 99%